An Analysis of Capital Structure, Stock Ownership Structure, and Profitability as Intervening Variables in Firm Value Testing - Ni Komang Septia Noriska; Mehilda Rosdaliva; Marcelinus Anggun Dananto Kuncorojati (Jurnal Multidisiplin Madani, 2023)
Value is one metric that identifies a company's sustainability. Financing assets or paying off a company's debt are two alternatives to the capital structure and stock ownership structure. Businesses can also use profitability indicators to decide whether a capital structure is necessary and how much stock should be owned. The purpose the The link between capital structure and return, as well as the profitability of capital structure for each of these attributes on equity, were examined and empirically established in this study. business value. Manufacturing firms registered on the Indonesia Stock Exchange between 2014 and 2016 made up the sample population for this study. Additionally, the sample used for the 2014–2016 period included 10 manufacturing firms in the food and beverage subsector. Descriptive analysis and partial least squares (PLS) data analysis were the methods employed in this investigation. Indicators were also included as sub-variables affected by latent variables in a reflective model. The measurement model testing also made use of the outer and inner models. The study's findings showed that the latent variable of profitability is significantly influenced by the ownership structure of stocks and the capital structure. Furthermore, there is a connection between the latent variables of corporate value and profitability. the latent variables of business value or capital structure, however, are unaffected by the stock ownership structure